Connectivity between the volatility of green and non-green bond markets with international markets - Gálvez-Gamboa, Francisco (2024)
This research paper analyzes the spillover effects of volatility between the U. S. green and non-green bond markets with international market volatility between 2018 and 2023. The empirical work used time and frequency domain methodology to analyze the connectivity in the short, medium, and long term. The results demonstrate that both green and non-green bond markets are recipients of volatility, although green bonds receive volatility to a lesser extent than traditional bonds. Despite this, traditional bonds become recipients of volatility during periods such as the COVID-19 pandemic, while green bonds experience volatility reception during the Russia-Ukraine conflict period.